Editorial for Special Issue "Practices in Science and Engineering Education" - Yew-Jin Lee; Yann Shiou Ong (MDPI AG, 2024)
As Co-Editors of this Special Issue on science and engineering practices (SEP), we are delighted to curate five excellent submissions that have come our way over the last three years [...]